Synthesis of Atropisomers by Transition-Metal-Catalyzed Asymmetric C–H Functionalization Reactions - Liu, Chen-Xu; Zhang, Wen-Wen; Yin, Si-Yong; Gu, Qing; You, Shu-Li (Journal of the American Chemical Society, 2021)
Transition-metal-catalyzed enantioselective C–H functionalization has become a powerful strategy for the formation of C–C or C–X bonds, enabling the highly asymmetric synthesis of a wide range of enantioenriched compounds. Atropisomers are widely found in natural products and pharmaceutically relevant molecules, and have also found applications as privileged frameworks for chiral ligands and catalysts. Thus, research into asymmetric routes for the synthesis of atropisomers has garnered great interest in recent years. In this regard, transition-metal-catalyzed enantioselective C–H functionalization has emerged as an atom-economic and efficient strategy toward their synthesis. In this Perspective, the approaches for the synthesis of atropisomers by transition-metal-catalyzed asymmetric C–H functionalization reactions are summarized. The main focus here is on asymmetric catalysis via Pd, Rh, and Ir complexes, which have been the most frequently utilized catalysts among reported enantioselective C–H functionalization reactions. Finally, we discuss limitations on available protocols and give an outlook on possible future avenues of research.